Socialization of Literacies Assessment in the Covid-19 Pandemic Era for Elementary School Teachers in the Province of Jakarta in Indonesia - MS, Zulela; Marini, Arita; Safitri, Desy; Lestari, Ika; Zahari, Musril; Iskandar, Rossi; Sudrajat, Ajat; Nuraini, Sri; Rihatno, Taufik; Suntari, Yustia; Nafiah, Maratun; Rosinar, Rosinar (International Journal of Community Service Learning, 2022)
Partner of this international collaboration of community service is RMIT University in Australia, Prof. Dr. Heather Fehring, to be invited to collaborate in giving socialization about effective literacies assessment in the covid-19 pandemic era to encourage development of elementary school teachers’ competences in the province of Jakarta in Indonesia.  Location of this international collaboration of community service is in the Province of Jakarta in Indonesia.  The target of this community service is elementary school teachers in the Province of Jakarta in Indonesia.  The problem with the target audiences is that the elementary school teachers’ competences in the province of Jakarta in Indonesia to deal with effective literacies assessment in the covid-19 pandemic era has not been optimal.  In addition to this, the socialization of effective literacies assessment in the covid-19 pandemic era for elementary school teachers in the Province of Jakarta in Indonesia has not been done before.  In order to develop elementary school teachers’ competences in the province of Jakarta in Indonesia in dealing with literacies assessment in the covid-19 pandemic era to achieve optimal learning quality, the solution is socialization of effective literacies assessment in the covid-19 pandemic era for them.  The output targets to be achieved in this international collaboration of community service are pocket book, certificates, videos on YouTube, articles in journal of community service, publications in mass media, Intellectual Property Rights (IPR), seminar, report.The methods used in conducting this international collaboration of community service are cooperative learning, problem-based learning, and giving assignments.  This socialization is conducted through video conferences in the form of learning activities to improve the competence in dealing with effective literacies assessment in the covid-19 pandemic era to achieve optimal learning quality for elementary school teachers in the province of Jakarta in Indonesia. The socialization of virtual classroom given is related to technical guidelines of effective literacies assessment implementation in order to achieve optimal learning quality. This international collaboration of community service is conducted at elementary schools in the Province of Jakarta in Indonesia because those elementary schools are regularly coached by Universitas Negeri Jakarta.  Evaluation of process and results is done to find out the competences of elementary school teachers in the province of Jakarta in Indonesia in dealing with effective literacies assessment in the covid-19 pandemic era to achieve optimal learning quality.  This international collaboration of community service is started with a pre-test about effective literacies assessment implementation to know the prior knowledge of target audiences about effective literacies assessment and ended with a post-test after socialization is completed to determine the success of implementing this activity.